Abell 2744: too much substructure for [Lambda] CDM? - Schwinn, Johannes; Bartelmann, Matthias (Monthly notices of the Royal Astronomical Society, 2017)
The massive substructures found in Abell 2744 by Jauzac et al. present a challenge to the cold dark matter paradigm due to their number and proximity to the cluster centre. We use one of the biggest N-body simulations, the Millennium XXL, to investigate the substructure in a large sample of massive dark matter haloes. A range of effects that influence the comparison with the observations is considered, extending the preliminary evaluation carried out by Jauzac et al. There are many tens of haloes in the simulation with a total mass comparable with or larger than that of Abell 2744. However, we find no haloes with a number and distribution of massive substructures (>5 × 1013 M⊙) that is close to that inferred from the observations of Abell 2744. The application of extreme value statistics suggests that we would need a simulation of at least 10 times the volume of the Millennium XXL to find a single dark matter halo with a similar internal structure to Abell 2744. Explaining the distribution of massive substructures in clusters is a new hurdle for hierarchical models to negotiate, which is not weakened by appeals to baryonic physics or uncertainty over the nature of the dark matter particle.